2020
DOI: 10.24200/jonus.vol5iss2pp261-281
|View full text |Cite
|
Sign up to set email alerts
|

Professional Counsellors’ Perceptions and Experiences of Multicultural Counselling in Malaysia: A Qualitative Study

Abstract: Background and Purpose: The contemporary status of multicultural counselling field in Malaysia is ambiguous as there is limited research in this field. Even though Malaysia is deemed as a multicultural nation, there are still some issues and concerns with regards to the understanding and practice of multicultural counselling. Hence, the present research aims to: (a) explore the definitions of the term ‘multicultural counselling’ as perceived by professional counsellors; (b) identify the dimensions of multicult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Furthermore, the results of the study show that there is no significant relationship between the level of multicultural counseling competency and length of service. The results of this study are in line with the findings of the respondents who stated competency will be improved through personal experience and continuous multicultural counseling practice especially throughout the service (Jaladin et al, 2020). This means that the duration of professional experience has nothing to do with the level of competency.…”
Section: Difference In Level Of Multicultural Counseling Competency B...supporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, the results of the study show that there is no significant relationship between the level of multicultural counseling competency and length of service. The results of this study are in line with the findings of the respondents who stated competency will be improved through personal experience and continuous multicultural counseling practice especially throughout the service (Jaladin et al, 2020). This means that the duration of professional experience has nothing to do with the level of competency.…”
Section: Difference In Level Of Multicultural Counseling Competency B...supporting
confidence: 85%
“…Furthermore, it has an impact on the self-efficacy and efficiency of school counselors in conducting effective guidance and counseling services. The contemporary status of the field of multicultural counseling in Malaysia is still unclear as there is limited research in this field as there are still some issues that need to be addressed in relation to the understanding and practice of multicultural counseling (Jaladin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have pointed out that the contemporary status of multicultural counseling in Malaysia remains unclear, due to the lack of studies in this field (Voon & Jaladin, 2017). Besides, Rafidah Aga Mohd Jaladin et al (2020) have listed a few serious concerns about (a) cultural relevance of counselling theories applied by Malaysian counsellors, (b) the extent of adjustment or modification, made by Western-trained counsellors based on Malaysian"s culture, and (c) the status of multicultural counseling practices among professional counsellors. Therefore, it is suggested that there is an imminent need for Malaysian professional counsellors to improve their multicultural counseling competencies.…”
Section: Introductionmentioning
confidence: 99%